KODE SASTRA DALAM SYAIR DIDONG - Ismawirna Ismawirna; Erfinawati Erfinawati; Manis Fitri Binti Binti (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2022)
The study is titled“Literature Code In Didong Poetry”.The problem formulation in this research is